Embedding trauma-informed, culturally sensitive, and compassionate care training in health and social care curricula: Evaluation of a multidisciplinary student intervention utilizing a pre- post-test survey design - Frankie J. Fair; Catherine Burke; Hora Soltani (PLoS ONE, 2026)
Introduction There were an estimated 281 million international migrants across the globe in 2020. Additionally, 30.5% of people globally have been exposed to four or more traumatic events. Providing equitable, trauma aware, culturally sensitive, and compassionate healthcare services is a priority to meet evolving health and social care requirements. This study aimed to evaluate trauma aware, culturally sensitive, and compassionate care training for health and social care students. Methods We previously co-produced and evaluated trauma aware, culturally sensitive, and compassionate care training among midwives, with positive results across three European countries. We adapted this training for a wider range of healthcare professionals and delivered it to 1,400 students from midwifery, nursing, and other health and social care disciplines. A pre-test post-test study design using pre- and post-seminar questionnaires and a reflective paragraph submitted two months after the training evaluated the training and its impact on practice. Descriptive statistics and Mann Whitney U-tests were undertaken on quantitative data and simple content analysis on qualitative data. Results Significant improvements were seen between mean pre- and post-seminar scores in all domains of students’ self-perceived capability including providing culturally sensitive care (p < 0.001), trauma aware care (p < 0.001), and compassionate care (p = 0.001). Open ended responses revealed three themes. Students identified “enhanced knowledge”, alongside “contextual influences” which acted as barriers and facilitators that impacted on “reflection and implementation in practice”. Conclusion Training in trauma aware, culturally sensitive, and compassionate care improved students’ confidence and competence, with positive evaluations and opportunities to directly put learning into clinical practice. Incorporating such training into undergraduate curricula is essential to equip health and social care professionals for the complexities of everyday practice. Future research should place particular emphasis on evaluating students’ actual implementation of the training into practice, for example through video-taped mock clinical encounters, as well as determine the impact of training on patient clinical outcomes and experiences of care.